Trends in the treatment of cytomegalovirus infection in oncohematological patients - D. N. Balashov (Онкогематология, 2014)
Cytomegalovirus (CMV)-related complications remain an extremely serious and urgent problem in immunocompromised patients. Ganciclovir (GCV) is efficient for the treatment of CMV-infection, but myelotoxicity limits the possibilities of their application. In addition, prolonged or intermittent courses of antiviral drugs predispose to the development of CMV drug-resistant strains. Valganciclovir is a safe and effective alternative to intravenous GCV. Despite the well-spread application of effective methods of early detection and pre-emptive treatment, the issue of the control of CMV-infection is not resolved. High intensive immunoablative therapy (alemtuzumab, ATG, еtс.) and hematopoietic stem cell transplantation (HSCT) from alternative donors greatly increase the risk of life-threatening visceral CMV-infections in patients. Thereby, studies of new therapeutic approaches (for example, transfusion of CMV-specific T-cells) are actually in process.